Validity of clinical and sonographic diagnosis of IUGR: a comparative study - Marhatta, Nisha; Kaul, Indu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: IUGR refers to a condition in which a fetus is unable to grow to its genetically predetermined potential size. It is the major cause of perinatal morbidity and mortality in developing countries. The present study was conducted to compare the validity of clinical diagnosis against sonographic diagnosis of IUGR. Methods: This study was conducted in the department of Obstetrics and Gynaecology, SMGS Hospital, Jammu from Octobar 2013 to September 2014. It included 247 women with singleton pregnancies with longitudinal lie. They underwent serial clinical assessment using SFH, AG and weight gain along with Ultrasound and Doppler of Umbilical & Middle cerebral artery. Birth weight of newborns was measured at delivery and was thereafter correlated with clinical and sonographic diagnosis; to access their validity. Results: Sensitivity of SFH in detecting IUGR was 71.4% against 75.7% by Ultrasound and was highest with Doppler of 82.9%. Specificity was 43.6% by SFH, 64.3% by Ultrasound and 86.2% by Doppler. Doppler also had the highest NPV of 92.6% against 79.1% by SFH and 86.8% by Ultrasound. The combination of clinical and ultrasound diagnosis increased the sensitivity to 95.2% and NPV to 95.91%. However, the combination of clinical and Doppler assessments did not significantly change the outcome. Conclusions: Doppler is the single best investigation available for diagnosing IUGR with a high specificity and NPV. However, importance of clinical diagnosis cannot be overlooked, especially in a developing country with limited resources like ours. In the absence of Doppler combined clinical and Ultrasound assessment should be considered.